2014
DOI: 10.1158/0008-5472.can-13-2545
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-to-Inosine RNA Editing Mediated by ADARs in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC), the major histologic form of esophageal cancer, is a heterogeneous tumor displaying a complex variety of genetic and epigenetic changes. Aberrant RNA editing of adenosine-to-inosine (A-to-I), as it is catalyzed by adenosine deaminases acting on RNA (ADAR), represents a common posttranscriptional modification in certain human diseases. In this study, we investigated the status and role of ADARs and altered A-to-I RNA editing in ESCC tumorigenesis. Among the three ADAR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
185
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(200 citation statements)
references
References 34 publications
13
185
2
Order By: Relevance
“…Thus, levels of editing in mature mRNAs may also be regulated by differential splicing. Moreover, Flnb editing has been shown to be altered in esophageal and liver carcinomas due to the increased activity of ADAR1 indicating that this enzyme may also target Flnb , at least under specific conditions [38,39]. Clearly, further investigations concerning the modulation of Flnb RNA editing will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, levels of editing in mature mRNAs may also be regulated by differential splicing. Moreover, Flnb editing has been shown to be altered in esophageal and liver carcinomas due to the increased activity of ADAR1 indicating that this enzyme may also target Flnb , at least under specific conditions [38,39]. Clearly, further investigations concerning the modulation of Flnb RNA editing will be required.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ADAR1 is also downregulated by miRNA-1 (miR-1) [16,17], and the tight regulation of ADAR1 by miR-1 is likely to be critical for heart development [18,19]. In ESCC, we found that ADAR1 gene, which is mapped to chromosome 1q21, was amplified in approximately 70% of ESCC tumors using fluorescent in situ hybridization, and there was a positive correlation between overexpression of ADAR1 and the genomic amplification of ADAR1 gene in ESCC specimens [11], suggesting another mechanism of ADAR1 overexpression in tumors.…”
Section: Adar1 Expression and Localizationmentioning
confidence: 87%
“…Our recent studies have reported that the differential expression of ADAR1 and/or ADAR2 was observed in HCC and ESCC tumors, leading to a gene-specific hyper or hypo-editing phenotype [11,25,33]. In ESCC, ADAR1 and ADAR2 were abundantly expressed, whereas ADAR3 was undetectable.…”
Section: Adar1 a Prognosis Marker In Esccmentioning
confidence: 98%
See 2 more Smart Citations